Selective extraction of cesium from high concentration rubidium chloride leach liquor of lepidolite - Lv, Yingwei; Ma, Baozhong; Liu, Yubo; Wang, Chengyan; Zhang, Wenjuan; Chen, Yongqiang (Desalination, 2022)
A special extractant, 4-tert-butyl-2-(α-methylbenzyl) phenol (t-BAMBP), was applied in cesium separation and purification from high concentration of rubidium chloride leach liquor. Effects of various parameters, such as feed liquid alkalinity, reagent concentration, contact time, and phase ratio, on extraction, scrubbing and stripping were systematic studied. The results demonstrated that the extraction rate of cesium reached 99.18% after five-stage countercurrent extraction, with the optimal extraction conditions that a feed liquid initial alkalinity of 10 g/L, t-BAMBP concentration of 1 mol/L, contact time of 1 min, and phase ratio (O/A) of 1:4. In addition, the loaded organic phase coextracted impurity elements (15.78% Rb, 0.5% K) was scrubbed with 0.1 mol/L HCl. After four-stage countercurrent scrubbing, the scrubbing rates of rubidium and potassium were 99.83% and 100% respectively, as well as 5.73% of cesium was lost. Almost all cesium (99%) was stripped with 0.05 mol/L HCl by two-stage countercurrent stripping after the organic phase was scrubbed. The slope method calculated the composition of the extraction complex as CsOR ∙ 2ROH(o), and the cation exchange reaction was proven to be the extraction mechanism. [Display omitted] •Extraction of Cs from lepidolite leach liquor with high concentration RbCl.•The extraction rate of Cs was 99.18% after five-stage countercurrent extraction.•High scrubbing rates of impurity elements were obtained under 0.1 mol/L HCl.•The cation exchange reaction was proven to be the extraction mechanism.